A Five Year financial plan of Mc Philips Food Industrial, Inc - Carpio, Ivan James P. 4 0 16; 5 (2017)
EXECUTIVE SUMMARY: This study is designed to create a five-year financial plan for Mc Philips Food Industries Inc. The entity is a quick service restaurant operating in the Philippines. It is a franchisee of McDonald's Philippines which currently has six branches. The main problem of the entity is mainly focused on the improvement of the entity's profitability by minimizing its incurred controllable expenses. The analysts used a five year audited financial statements of the entity from 2011-2015, and an interim or unaudited financial statement of 2016 to make a financial analysis of the entity's problem. After a thorough and critical analysis of the entity's internal and external environment, financial and historical ratios through its financial statements, the analysts came up to have three alternative courses of actions to put solution to the entity's identified problems. Namely the Cutback in Direct Labor by and Tight Inventory Management. The Cutback in Direct Labor is used to reduce the number of employees on duty daily. While the Tight Inventory Management is used to reduce waste and spoilage cases and increase of storage capacity to decrease sold out tendencies. Lastly, the Controlling of other Overhead Costs and Expenses. Among these alternative courses of action, the analysts have chosen to recommend Controlling of other Overhead Costs and Expenses as this is the best alternative suited for the entity to address all of its identified problems. With the use of forecased historical financial statements of the entity, the analysts of this study are able to project the financial statements of the entity after employing the selected course of action.
Financial Plan: (BSBA Major in Finance and Treasury Management) - Pamantasan ng Lungsod ng Maynila, 2017.
Keywords: 2 -- 0; 6; 20; 20; 2